Interpretation of a Local Museum in Thailand - Jirawan Sirivanichkul; Koompong Noobanjong; Supornchai Saengratwatchara; Weeranan Damrongsakul; Chaturong Louhapensang (My University, 2018)
This paper considers the interpretation of a local museum in Thailand using the local museum of Thai Bueng Khok Salung as a case study. Data collection was carried out from 9 September 2015 to 22 January 2018. The collected data were derived from related documents, previous studies, in-depth interviews and observations. This present research aimed to investigate the interpretation of the case study through the management of “persons, places, and things”. The findings revealed that there are two major types of interpretation at the museum: the interpretation for the people in the community (that is, indigenous curators, local visitors, and local people) and the interpretation for the people outside the community (that is, general visitors and specific-purpose visitors). The results of the study indicate an appropriate and effective interpretation system for the specific community context which encourages people—both locals and foreigners—to be aware of the value of the community. Consequently, as a result of their awareness, people would increasingly cherish their community and work in collaboration with other people for the sustainable development of the community.
Keywords: Local Community; Value (mathematics); Community Development; Museums and Cultural Heritage